The Impact of childhood maltreatment on the alliance in the treatment for persistent depression: analyses on the differential effects of the cognitive behavioral analysis system of psychotherapy and supportive psychotherapy - Eich, Hannah Sophie (2019)
The present dissertation investigated the impact of childhood maltreatment (CM) and the differential effects of the disorder-specific Cognitive Behavioral Analysis System of Psychotherapy (CBASP) and nonspecific Supportive Psychotherapy (SP) on the alliance. The alliance was assessed by the German Helping Alliance Questionnaire (HAQ), whose psychometric quality was examined for that purpose. Analyses relied on data from a randomized-controlled clinical trial which compared CBASP to SP in the treatment of 268 early-onset persistently depressed outpatients. Both treatments ran in parallel and consisted of 32 individual sessions over the course of 48 weeks. The first study explored the psychometrics of the German HAQ for patients (HAQ-P) and therapists (HAQ-T). Results indicated that the HAQ is internally consistent and may be used unidimensionally to assess a global helping alliance or two-dimensionally to examine the two subscales ‘relation to the patient/therapist’ and the ‘satisfaction with therapeutic outcome’. Analyses on convergent validity to a measure of interpersonal problems found small significant correlations. The second study investigated how both dimensions of the alliance developed over time, if CBASP had a superior effect on the mean alliance ratings, and whether there were differential effects of CBASP and SP on the course of alliance between patients with low versus medium versus high CM. Findings indicated an improvement of alliance in both treatments and that CBASP led to more positive overall mean alliance ratings. Only in the group of patients with high CM did CBASP have a distinctly more positive effect on the increase in alliance ratings: Patients with high CM receiving CBASP rated the alliance increasingly more favourable than patients who received SP. This effect was more pronounced on the subscale ‘satisfaction with therapeutic outcome’. Together, the two studies demonstrated that the German HAQ provides an adequate instrument for the uni- and two-dimensional measurement of the alliance. Patients perceived the alliance, as assessed by the HAQ-P, increasingly positive over the course of both CBASP and SP. In comparison to the nonspecific treatment, there appears to be an overall positive effect of CBASP on both dimensions of the alliance, that is, ‘relation to therapist’ and ‘satisfaction with therapeutic outcome’. Only in the group of patients with high CM, did CBASP have a more favourable effect on the increase in alliance ratings, which was particularly large on the ‘satisfaction with therapeutic outcome’.
Keywords: Hochschulschrift